The Emergence of Inner Speech and Its Measurement in Atypically Developing Children - Vissers, Constance Th. W. M.; Tomas, Ekaterina; Law, James (Frontiers in Psychology, 2020)
Inner speech (IS) occurs in humans regardless of their cultural and linguistic background, suggesting its key role in human cognition. The absence of overt articulation leads to methodological challenges to studying IS and its effects on cognitive processing. Investigating IS in children is particularly problematic due to cognitive demands of the tasks and age restrictions for collecting neurophysiological data; thus, the developmental aspects of IS remain poorly understood despite the long history of adult research. Studying developmental aspects of IS could shed light on the variability in types and amount of IS in adults. In addition, problems in mastering IS might account for neuropsychological deficits observed in children with neurodevelopmental conditions. For example, deviance in IS development might influence these children’s general cognitive processing, including social cognition, executive functioning and related social-emotional functioning. The aim of the present paper is to look at IS from a developmental perspective, exploring its theory and identifying experimental paradigms appropriate for preschool and early school-aged children in Anglophone and Russian literature. We choose these two languages because the original work carried out by Vygotsky on IS was published in Russian and Russian scientists have continued to publish on this topic since his death. Since the 1960s much of the experimental work in this area has been published in Anglophone journals. We discuss different measurements of IS phenomena, their informativeness about subtypes of IS and their potential for studying atypical language development. Implications for assessing and stimulating IS in clinical populations are discussed.